Nanocarbons for Biology and Medicine: Sensing, Imaging, and Drug Delivery - Panwar, Nishtha; Soehartono, Alana Mauluidy; Chan, Kok Ken; Zeng, Shuwen; Xu, Gaixia; Qu, Junle; Coquet, Philippe; Yong, Ken-Tye; Chen, Xiaoyuan (Chemical reviews, 2019)
Nanocarbons with different dimensions (e.g., 0D fullerenes and carbon nanodots, 1D carbon nanotubes and graphene nanoribbons, 2D graphene and graphene oxides, and 3D nanodiamonds) have attracted enormous interest for applications ranging from electronics, optoelectronics, and photovoltaics to sensing, bioimaging, and therapeutics due to their unique physical and chemical properties. Among them, nanocarbon-based theranostics (i.e., therapeutics and diagnostics) is one of the most intensively studied applications, as these nanocarbon materials serve as excellent biosensors, versatile drug/gene carriers for specific targeting in vivo, effective photothermal nanoagents for cancer therapy, and promising fluorescent nanolabels for cell and tissue imaging. This review provides a systematic overview of the latest theranostic applications of nanocarbon materials with a comprehensive comparison of the characteristics of different nanocarbon materials and their influences on theranostic applications. We first introduce the different carbon allotropes that can be used for theranostic applications with their respective preparation and surface functionalization approaches as well as their physical and chemical properties. Theranostic applications are described separately for both in vitro and in vivo systems by highlighting the protocols and the studied biosystems, followed by the toxicity and biodegradability implications. Finally, this review outlines the design considerations for nanocarbon materials as the key unifying themes that will serve as a foundational first principle for researchers to study, investigate, and generate effective, biocompatible, and nontoxic nanocarbon materials-based models for cancer theranostics applications. Finally, we summarize the review with an outlook on the challenges and novel theranostic protocols using nanocarbon materials for hard-to-treat cancers and other diseases. This review intends to present a comprehensive guideline for researchers in nanotechnology and biomedicine on the selection strategy of nanocarbon materials according to their specific requirements.